Bibliometric analysis of Integrated Marketing Communications (2015–2024): knowledge structures, emerging themes, and future perspectives - Qi, Meng; Abdullah, Zulhamri; Zhou, Baiyu; Abdul Rahman, Saiful Nujaimi (Springer Nature, 2025)
Integrated Marketing Communication (IMC) research has expanded rapidly, but its intellectual structure remains fragmented, limiting theoretical consolidation and practical advancements, especially in this digital era. This study conducts a bibliometric analysis of IMC literature from 2015 to 2024 using Scopus data, employing co-occurrence analysis, citation mapping, and network visualization. The findings reveal dominant research themes, including digital transformation, consumer engagement, and brand equity, alongside emerging topics such as AI-driven personalization and cross-platform integration. Key scholars, influential journals, and collaborative networks are identified, highlighting the field’s evolution and interdisciplinary connections. This study provides a thorough overview of the intellectual landscape of IMC over the past decade, offering strategic directions for future research and practical insights for marketing professionals navigating an increasingly digital environment.